Developing Multimedia-Based Interactive Learning Media on Football Learning Courses - Ahmad Al Munawar; Dicky Hendrawan (Journal Physical Education, Health and Recreation, 2020)
The purpose of this study is to develop multimedia-based interactive learning media on football subject. This research method is R&D, development research where product development consists of four steps namely (1) Define, (2) Design, (3) Development and (4) Dissemination. The population and sample in this study were all class students of 2017 who took football courses at STOK of Bina Guna Medan. Data collection techniques were conducted by observation, interview and questionnaire. The testing phase was carried out with product validation by two media experts, and two material experts, as well as testing on users (students). The data analysis technique used is descriptive analysis technique. The results of this study are: (1) based on two media experts, the score is 83.33 with the category “very appropriate” to be used as a learning medium. (2) based on two material experts, the score was 71.53 with the appropriate category to be used as learning media. (3) based on the assessment by the students gained a total score of 75.90 with the category "very appropriate" as a learning media. Based on the above results, multimedia-based interactive learning media on football learning subject can be used as learning media.